Inducing Immunity Where It Matters: Orthotopic HPV Tumor Models and Therapeutic Vaccinations - Zottnick, Samantha; Voß, Alessa L.; Riemer, Angelika B. (Frontiers in Immunology, 2020)
Anogenital and oropharyngeal cancers caused by human papillomavirus (HPV) infections account for 4.5 % of all cancer cases worldwide. So far, only the initial infection with selected high-risk types can be prevented by prophylactic vaccination. Already existing persistent HPV infections, however, can currently only be treated by surgical removal of resulting lesions. Therapeutic HPV vaccination, promoting cell-based anti-HPV immunity, would be ideal to eliminate and protect against HPV-induced lesions and tumors. A multitude of vaccination approaches has been tested to date, many of which led to high amounts of HPV-specific T cells in vivo. However, growing evidence suggests that not the induction of systemic but of local immunity is paramount for tackling mucosal infections and tumors. Therefore, recent therapeutic vaccination studies have focused on how to induce tissue-resident T cells in the anogenital and oropharyngeal mucosa. These approaches include direct mucosal vaccinations and influencing the migration of systemic T cells towards the mucosa. The efficacy of these new vaccination approaches is best tested in vivo by utilizing orthotopic tumor models, i.e. HPV-positive tumors being located in the animal’s mucosa. In line with this, we here review existing HPV tumor models and describe two novel tumorigenic cell lines for the MHC-humanized mouse model A2.DR1. These were used for the establishment of an HPV16 E6/E7-positive vaginal tumor model, suitable for testing therapeutic vaccines containing HLA-A2-restricted HPV16-derived epitopes. The newly developed MHC-humanized orthotopic HPV16-positive tumor model is likely to improve the translatability of in vivo findings to the clinical setting.